Creutzfeldt-Jacob disease: An autopsy case report in tertiary care hospital - Nitin M Gadgil (Indian Journal of Pathology and Microbiology, 2012)
Sporadic Creutzfeldt-Jakob disease (CJD) is the most common prion disease. It is a rare, fatal neurodegenerative disease caused by an infectious protein called prion. The diagnosis can be confirmed only by histological examination of brain tissue. Because of the transmissible nature of the disease, autopsy or brain biopsy cannot be performed at many institutions. Histology shows spongiform changes, neuronal loss, reactive astrocytic proliferation, accumulation of pathologic protein occurring in three general forms: Sporadic, familial, and acquired form, including a variant form of CJD. It clinically presents as predominantly progressive dementia with a rapid onset, myoclonus, cerebellar, pyramidal, extra pyramidal and visual signs. Occurrence of periodical spikes in electro-encephalogram, observation of cortical signal alterations in magnetic resonance imaging (MRI) studies, and detection of protein 14-3-3 in cerebrospinal fluid substantiate diagnosis. Autopsy case is presented of a 50 year old woman with progressive dementia, typical neurological symptoms, MRI findings and confirmation of CJD on histology and immunostaining.